Kedudukan Perjanjian Perkawinan Yang Dibuat Setelah Perkawinan Dilangsungkan Terhadap Pihak Ketiga - D., Ida Bagus Adhitya Prayoga; Yustiawan, Dewa Gede Pradnya (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 01 (2022), 2022)
The purpose of this paper is to determine the arrangement of the marriage agreement before the decision of the constitutional court number 69/PUU-XII/2015 and the position of the marriage agreement made after the marriage took place against a third party. The method used in this research is the normative method and the type of approach used is the law and conceptual. Marriage agreements are more about property and there is no clear understanding of this. Marriage is regulated in Law Number 1 of 1974 concerning Marriage and the marriage agreement is regulated in Article 29 of Law Number 1 of 1974 which discusses the time of making a marriage agreement. Prior to the Constitutional Court Decision Number 69/PUU-XIII/2015, prospective husband and wife who will make a marriage agreement must comply with Law Number 1 of 1974 concerning Marriage, namely Article 29 paragraph (1) which discusses the time of making of the marriage contract. marriage agreement. In the Decision of the Constitutional Court number 69/PUU-XII/2015 which allows the marriage contract to be made after marriage, it will have an impact on third parties related to debt. Marriage agreements relate to third parties starting from the registration of the agreement.